2020
DOI: 10.1371/journal.pone.0230139
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations and socioeconomic determinants of modern contraceptive use in Ghana: A Bayesian multilevel analysis

Abstract: The literature on spatial patterns and contextual factors affecting modern contraceptive use is not well-documented in Ghana. This study describes the spatial variations and estimates the socioeconomic determinants of modern contraception among women in reproductive age in Ghana. Using data from the 2014 Ghana Demographic and Health Survey, both global and local Moran's I test were performed to show spatial autocorrelation and Bayesian multilevel models estimated to determine socioeconomic factors affecting mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 14 publications
4
45
0
1
Order By: Relevance
“…Family planning and contraception play an important role in reducing maternal morbidity and mortality by preventing unintended pregnancies (Atakro et al, 2019; Nyarko, 2020). This is in line with the Sustainable Development Goal (SDG) that focuses on ensuring healthy lives and promoting well-being for everybody at all ages (Nyarko, 2020; Pradhan et al, 2017; UNCG SDGs, 2017). Also, Ghana’s population has continued to increase at large rates (Cooke et al, 2016; Kpessa-Whyte, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family planning and contraception play an important role in reducing maternal morbidity and mortality by preventing unintended pregnancies (Atakro et al, 2019; Nyarko, 2020). This is in line with the Sustainable Development Goal (SDG) that focuses on ensuring healthy lives and promoting well-being for everybody at all ages (Nyarko, 2020; Pradhan et al, 2017; UNCG SDGs, 2017). Also, Ghana’s population has continued to increase at large rates (Cooke et al, 2016; Kpessa-Whyte, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Religion is one such factor affecting the use of contraceptives in Africa (Gyimah et al, 2012; Laryea et al, 2016); A study showed that Muslim and Traditional women in Ghana, were more likely to have never used any form of contraceptive (Gyimah et al, 2012). Socio-economic and contextual factors such as proximity to health facilities also affect contraceptive use in Ghana (Nyarko, 2020). A study showed that women who were either uneducated, unemployed, or never-married were most likely to never use any form of contraceptive (Nyarko, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The use of modern contraceptives and its associated factors among women age (15–49 years) have been documented in Ghana [ 9 , 11 16 ]. However, utilization of modern contraceptives specifically among women with induced abortion history is underreported despite their vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…Reported prevalence rates of contraceptive use among women have been 18% (ages 16-19 years), 49.2% (ages 13-18 years), and 44% (ages 18-24 years) (Agyemang et al, 2019;Grindlay et al, 2018;Odonkor et al, 2012).. The reports show that modern contraceptives use vary across the regions of Ghana (Nyarko, 2020), with an annual increase of about 3.66% (2.81-4.47%) among those aged 15-49 years (Ahmed et al, 2019). Factors such as place of residence, education, (Aviisah et al, 2018), occupation, marriage (Agyemang et al, 2019, reading newspapers, and watching television (Appiah et al, 2020) are believed to influence contraceptives use.…”
Section: Introductionmentioning
confidence: 99%